Influence Brand Experience, Perceived Quality, And Brand Love On Brand Loyalty For Purchasing Janji Jiwa Products - Rahayu, Ristiana; Ruswanti, Endang (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to analyze the influence of variables brand experience, perceived quality, value, brand love to brand loyalty. This research uses a quantitative method approach through techniques purposive sampling. This research obtained 192 respondents, respondents aged 18-35 years, domiciled in JABODETABEK (Jakarta, Bogor, Depok, Tangerang, Bekasi), and had purchased Janji Jiwa products more than once. This research uses the method Structural Equation Model Partial Least Square (SEM-PLS).The results of this research show brand loyalty formed because it is influenced by value and brand love. Next, increase perceived quality influenced by brand experience, brand experience and perceived quality influence on value. The findings of this research can be used as an assessment of the Janji Jiwa product in increasing customer loyalty. Janji Jiwa’s brand is a coffee shop in Indonesia that is liked by many people. A positive customer experience regarding the purchase of Janji Jiwa products can expand the Janji Jiwa brand.